Economic crisis and fiscal federalism in Italy - Maria Ambrosanio; Paolo Balduzzi; Massimo Bordignon (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2014)
For almost two decades, starting from the early `90s, Italy experienced the strongest wave of decentralization reforms in its post II World War history. The causes were both economic and political. Yet, in recent years, again economic and political causes seem to call for opposite reforms. Along with a second wave of scandals, this time interesting local politicians, the crisis that has hit our country since 2008 is having relevant effects on the relationships between central and local governments. The aim of this paper is to assess dimension and direction of these effects. We first review the situation of "fiscal federalism" in Italy before the crisis, summarizing the decentralization process in the `90s, its consequences in terms of financing and functions for local governments, the constitutional reform of 2001 and the implementation problems this created. We then look at the numbers of the crisis; the "double dip" of the economic cycle in the period 2007- 2013, the policies implemented to contrast the financial market confidence crisis and the distribution of the burden of the fiscal consolidation across levels of government. We also discuss the institutional features of the implemented policies, in particular referring to number of local governments and to the financial relationships between level of governments, including taxes, transfers, fiscal rules and bankruptcy procedurals. Finally, we look at the future: what consequences will the new European rules, as enshrined in the new art. 81, have on the financial relationships between levels of government? And how is the balance of power between the center and the periphery going to change in lieu of the new proposed Constitutional reform?
Keywords: H50; H60; H70; 330; crisis; fiscal federalism; decentralization